2015
DOI: 10.5625/lar.2015.31.2.86
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three diagnostic assays for the identification ofHelicobacter spp. in laboratory dogs

Abstract: A number of Helicobacter species may confound experimental data because of their association with disease progressing in various kinds of laboratory animals. Screening of Helicobacter species is particularly desirable, because they are prevalent in commercial and research animal facilities. The aim of the present study was to compare three diagnostic methods [e.g. Helicobacter stool antigen kit (HpSA), polymerase chain reaction (PCR) and rapid urease test (RUT)] for the identification of Helicobacter spp. in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 26 publications
0
27
2
Order By: Relevance
“…This methodology renders the PCR more sensitive and theoretically allows the identification of up to two xenogenic cells in the analysed material. At the same time the use of two pairs of primers ensures the high specificity of this method and makes it possible to reject false positive results (Singh et al 2008, Hong et al 2015. The selection of primers and PCR reaction schemes are presented in Table 1.…”
Section: ' Amplicon II 5'mentioning
confidence: 99%
“…This methodology renders the PCR more sensitive and theoretically allows the identification of up to two xenogenic cells in the analysed material. At the same time the use of two pairs of primers ensures the high specificity of this method and makes it possible to reject false positive results (Singh et al 2008, Hong et al 2015. The selection of primers and PCR reaction schemes are presented in Table 1.…”
Section: ' Amplicon II 5'mentioning
confidence: 99%
“…In this study, using nested-PCR to assess stool samples, Helicobacter microorganisms were identified in 23% of animals. Hong et al (2015) obtained a higher percentage of gastric Helicobacter spp. DNA in faeces, amounting to 62.5%.…”
Section: Discussionmentioning
confidence: 92%
“…The large discrepancy in results in human and veterinary medicine may result from the small amount of gastric Helicobacter spp. in faeces, a degradation of bacterial DNA in the large intestine, the presence of polymerase inhibitors such as complex polysaccharides, and may depend on the DNA extraction method and type of PCR used (Kabir 2001, Shinozaki et al 2002, Falsafi et al 2009, Smith et al 2012, Hong et al 2015.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations